2022
DOI: 10.5796/electrochemistry.22-00045
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Electrolyte Decomposition at Cathode/Electrolyte Interface by Mg-Fe Binary Oxide Coating towards Room-Temperature Magnesium Rechargeable Battery Operation

Abstract: For practical room-temperature magnesium rechargeable battery operation, utilizing the nano-sized MgMn 2 O 4 spinel as cathode material is effective way to have high rate-capabilities; however, electrolyte decomposition at the cathode/electrolyte interface is inevitable. In this work, a Mg-Fe binary oxide is coated onto nano-sized MgMn 2 O 4 to form stable cathode electrolyte interface (CEI). This developed cathode material suppresses the electrolyte decomposition and improves the cyclability at room temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Figure f shows the discharge/charge cycles of the MMO treated at 300 °C. We previously confirmed the electrolyte decomposition at the same cell test condition by XPS analysis . Although the decomposition of electrolyte occurred competitively during overcharge, but we performed the cell test with the voltage range of 0.1–4.0 V to proceed the oxidation reaction.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Figure f shows the discharge/charge cycles of the MMO treated at 300 °C. We previously confirmed the electrolyte decomposition at the same cell test condition by XPS analysis . Although the decomposition of electrolyte occurred competitively during overcharge, but we performed the cell test with the voltage range of 0.1–4.0 V to proceed the oxidation reaction.…”
Section: Resultsmentioning
confidence: 59%
“…43,44 The on-site Coulomb correction (GGA+U) was used to describe the localized electronic states in the Mn 3d orbital (U Mn,d = 3.9 eV 45 ). The nudged elastic band (NEB) method 46 19,36 (n-Bu) 4 NMnO 4 was prepared according to a previous report. 47 2 mmol of (n-Bu) 4 NMnO 4 powder was first slowly added to a 2 mmol MgCl 2 solution made in a 25 mL ethanol and 25 mL diglyme mixture under vigorous stirring for 1 h. Ten milliliters of water was then injected to the brown colloidal solution, precipitating the MMO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that these problems can be overcome by coating the active material of the cathode. Coating materials used in the Mg cathode are reduced graphene oxide (rGO), V 2 O 4 , NH 4 VO 3 , phenylphosphonate, , Mg-Fe binary oxide, and further coating materials for MMB identified by computational analysis . These coating materials also achieved improved cycling ability.…”
Section: Introductionmentioning
confidence: 99%